The Challenges of Prosecuting Maritime Pirates - Wan Siti Adibah Wan Dahalan; Anati Binti Kisahi; Subasny Sevanathan; Muhammad Nasir (Faculty of Law, Sriwijaya University, Indonesia, 2020)
Maritime piracy has always posed a constant threat to the peace and security of maritime navigation. The rise of acts of piracy is found to have been caused by several crucial factors such as geographical factor, weak law enforcement, maritime insecurity, economic dislocation and cultural acceptability. Nevertheless, due to the lack of consistency and uniformity on the definition of piracy under international law as well as on the imposition of penalty or punishment for such acts, together with the lack of domestic laws on maritime piracy and the reluctance of States to prosecute maritime pirates, these have also contributed to the emergence and increase of such acts. Additionally, as a result, challenges are faced in prosecuting the captured maritime pirates, for instance, the drafting of the charges against the perpetrators, jurisdictional issues, political concerns and technical issues which may lead a State to drop the charges and releasing the perpetrators. Notwithstanding this, some States that do not have a specific legislation on piracy, such as Malaysia, had successfully tried and punished maritime pirates under their own domestic criminal laws. Accordingly, in order to face these challenges and to gradually eradicate the acts of piracy, it is suggested, amongst others, for the uniformity on the definition of piracy under international law, legal guidelines under the United Nations Convention on the Law of the Sea (UNCLOS) on the prosecution and imposition of punishment against maritime pirates and for States to increase their cooperation in combating acts of piracy via bilateral and multilateral treaties.